Impact of the COVID-19 pandemic on patients receiving intravitreal injections - Zhang Ningzhi; He Xuejun; Xing Yiqiao; Yang Ning (Archives of Biological Sciences, 2022)
We analyzed the economic benefits versus safety risks of sharing anti-vascular endothelial growth factor (VEGF) vials during the coronavirus disease (COVID-19) pandemic. This single-center retrospective study analyzed the data of patients with neovascular age-related macular degeneration (nAMD), proliferative diabetic retinopathy (PDR) and retinal vein occlusion (RVO) who received anti-VEGF between January 2016 and July 2021 at Renmin Hospital, Wuhan University, China. Costs were compared of the two protocols of intravitreal injections (IVIs) of ranibizumab, aflibercept and conbercept after (i) splitting the vial content for use in two patients and after (ii) disposal of the remaining vial content after use in a single patient, with the COVID-19 outbreak considered as the demarcation point. The incidence rates of post-injection endophthalmitis (PIE) pre- and post-outbreak were analyzed. The mean cost of a single IVI increased by 33.3%, from 3917.67±71.69 to 5222.67±84.98 Chinese Yuan during the pandemic. The incidences of IVI-related culture-positive PIE were 0.0134% (3 in 22448) and 0.0223% (1 in 4479), respectively, before and after the pandemic (P=0.6532). We conclude that vial sharing of IVIs in a large clinical institution is not associated with increased PIE risk and can significantly reduce the cost of therapy.